Identity Work and Organizational Identification. (July 2017) - Brown, Andrew D.
Abstract: In this paper, I analyse five approaches to identity work – discursive, dramaturgical, symbolic, socio‐cognitive, and psychodynamic – and show how these are helpful in exploring the ways people draw on their membership of organizations in their constructions of self, processes generally referred to as organizational identification. Collectively, these approaches constitute a distinctive perspective on identities and identifications which suggests that they are 'worked on' by embedded social actors who are both constrained and enabled by context. In so doing, I draw attention to issues of agency and process, the always dynamic and complex, often fractured, and sometimes contradictory nature of identities and identifications, and raise a series of issues and questions for further research.